Sequential injection system with amperometric immunosensor for sensitive determination of human immunoglobulin G - Chidkamon Thunkhamrak (2018)
© 2017 Elsevier B.V. Sequential injection (SI) system incorporated with amperometric immunosensor was developed for sensitive determination of human immunoglobulin G (HIgG). A cost effective label-free immunosensor was fabricated by immobilizing anti-HIgG on a graphene oxide (GO) modified screen-printed carbon electrode (SPCE). The developed electrode was characterized by cyclic voltammetry(CV), scanning electron microscope(SEM), and energy dispersive spectroscopy(EDS) which confirmed the selective immunointeraction of HIgG to the anti-HIgG on the electrode, thus reduced the amperometric current of [Fe(CN)6]3-/4-redox probe. The sensing electrode was placed in a designed electrochemical flow cell of SI system, where the redox probe was propelled through and the currents before and after the immunointeraction occurred were measured amperometrically by using a simple home-made amperometer. Under the optimum condition: flow rate of 2 mL min−1, applied potential of +350 mV, [Fe(CN)6]3-/4-concentration of 10 mM and 10 min of incubation time, a linear calibration in the range of 2–100 ng mL−1was achieved, with detection limit of 1.70 ng mL−1. The proposed system provided good repeatability and reproducibility and the application for urine sample analysis was demonstrated.